2020
DOI: 10.3390/environments7110103
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Political Determinants of Food Choices: A Preliminary Study in a Croatian Sample

Abstract: Production, processing, transporting, selling, and consumption of food are highly resource intensive. Therefore, if they are not well managed the consequences for the environment are far-reaching. This study aimed at investigating behaviors and attitudes of the Croatian population concerning the influence of environmental and political determinants of food choices, and the socio-demographic factors associated with pro-environmental behavior. Data analysis involved a non-probabilistic sample of 1534 adult parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…This agrees with previous studies where women reported low or no meat consumption and greener behavior [30]. Moreover, Croatian respondents were less likely to belong to the low or non-meat eater groups, as it seems that environmental issues are not associated to food choices in Croatia [31]. The group of heavy meat eaters was not explained by any sociodemographic characteristic.…”
Section: Public Health Nutrition Implicationssupporting
confidence: 90%
“…This agrees with previous studies where women reported low or no meat consumption and greener behavior [30]. Moreover, Croatian respondents were less likely to belong to the low or non-meat eater groups, as it seems that environmental issues are not associated to food choices in Croatia [31]. The group of heavy meat eaters was not explained by any sociodemographic characteristic.…”
Section: Public Health Nutrition Implicationssupporting
confidence: 90%
“…There is relevant confirmation that specific social norms linked to food consumption have a major effect on people's food choices. On the other hand, the globalization of food supply chains has increased the availability and variety of foods, becoming eventually less sustainable, owing to long distances travelled across the globe and/or being available throughout the entire year and not only in the production season [74][75][76].…”
Section: Discriminant Function Analysismentioning
confidence: 99%
“…Most studies report that food wastage is low in the Western Balkans, with respect to other more developed European countries, and highlight that consumers in the region have a positive attitude and are willing to reduce food wastage ( 14 , 15 , 19 , 21 – 23 , 25 ). However, Guiné et al ( 16 ) explore motivations influencing people's eating habits toward sustainability in 13 countries (viz.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Ilakovac et al ( 28 ) found that about two-thirds of the Croatian households consider FW bad for the environment. Matek Sarić et al ( 19 ) found that many different socio-demographic factors influence environmentally-concerned food choices in Croatia, such as age, gender, education level, and marital status. Knezevic et al ( 27 ) point out that concern about the environmental impacts is one factor affecting the attitude of Croatian university students toward FW.…”
Section: Resultsmentioning
confidence: 99%